PERAN KEPUASAN KERJA SEBAGAI MEDIASI PADA PENGARUH BUDAYA ORGANISASI, KOMITMEN ORGANISASI TERHADAP KINERJA GURU SMK WARGA SURAKARTA - Darmanta, Darmanta; Rispantyo, Rispantyo; Suprayitno, Suprayitno (JURNAL MANAJEMEN SUMBER DAYA MANUSIA, 2020)
This research is conducted in order to find out the significance of the influence of Organizational culture, organizational commitment and Job satisfaction on teacher performance, implemented in SMK Warga Surakarta. With a total population of 65 teachers. Data collection techniques using a questionnaire through validity and reliability tests. The data analysis technique uses multiple linear regression, t test, F test and R2 test which was previously tested using the classic assumptions. The results of the analysis coefficient determination R2 = 0.550 test means that the contribution of organizational culture, organizational commitment and job satisfaction to the performance SMK Warga teachers 55% is influenced by other factors. The analysis result shows that: organizational culture, organizational commitment significantly influenced the job satisfaction. Organizational culture organizational commitment and Job satisfaction significantly influenced on teacher performance, Job satisfaction does not significantly mediate organizational culture on teacher performance, Job satisfaction significantly mediates organizational commitment on teacher performance.